2015
DOI: 10.1590/s1516-89132015060298
|View full text |Cite
|
Sign up to set email alerts
|

Citotoxicity of Fipronil on Hepatocytes Isolated from Rat and Effects of Its Biotransformation

Abstract: The aim of this study was to characterize the mechanism of toxicity of fipronil on hepatocytes isolated from the rat and the effect of its biotransformation on the toxicological potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…The protective mechanisms toward oxidative stress mainly through balances mediated by non-enzymatic and enzymatic antioxidants 71 . In current study, the decrease in SOD and GPx activities of rats subjected to FIP might be due to the excess production of O 2 that is rapidly transformed by SOD and GPx to H 2 O 2 and water, respectively as reported in the liver of pregnant rats and their offspring due to the inadequate ROS detoxification produced by FIP in hepatocyte 33 , 66 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The protective mechanisms toward oxidative stress mainly through balances mediated by non-enzymatic and enzymatic antioxidants 71 . In current study, the decrease in SOD and GPx activities of rats subjected to FIP might be due to the excess production of O 2 that is rapidly transformed by SOD and GPx to H 2 O 2 and water, respectively as reported in the liver of pregnant rats and their offspring due to the inadequate ROS detoxification produced by FIP in hepatocyte 33 , 66 .…”
Section: Discussionmentioning
confidence: 57%
“…Several studies suggested that redox homeostasis disturbance was triggered during FIP toxicity was because of high ROS production 33 , 64 , 65 . Hepatotoxicity induced by FIP in this study might be due to increased levels of MDA and NO (the indicator of LPO) because of the high reactive oxygen metabolites production especially the hydroxyl radicals 33 , 66 , LPO play role in the disruption of the integrity of cellular membranes and implicated in liver injuries 67 . ROS can target cell membranes and other cellular molecules, resulting in protein oxidation, lipid peroxidation, caspase3 activation, and DNA damage 33 , 68 , leading to cell dysfunction 69 , 70 .…”
Section: Discussionmentioning
confidence: 71%
“…These findings indicated that FPN triggers intrinsic apoptosis via the mitochondrial signaling pathway that is initiated by the generation of ROS [56,58]. The mechanism of FPN toxicity involved its effect on mitochondrial bioenergetics and an alteration in calcium homeostasis, which led to a decrease in ATP synthesis with consequent cell death by necrosis [30]. Looking for potentially neuroprotective agents from natural products could attenuate oxidative stress-induced neurotoxicity might be helpful in the prevention and treatment of neurodegenerative disorders [63].…”
Section: Discussionmentioning
confidence: 99%
“…The first group (I) served as control; hence animals were orally given olive oil. The second group (II) was orally treated with FPN only (10.5 mg/kg BW) approximately 1/10 LD 50 [30]. The third group (III) was treated with combination of FPN (10.5 mg/kg BW) and TL methanol extract (TLE) (100 mg/kg BW) and finally the fourth group (IV) was orally treated with dissolved TLE only (100 mg/kg BW).…”
Section: Methodsmentioning
confidence: 99%
“…This synthetic chemical has great efficiency in controlling resistant/tolerant pest, which justifies its widespread use in several countries [6], although it is highly toxic for some animal species [12].…”
Section: Introductionmentioning
confidence: 99%